Attitude of Nurses towards Care of Elderly People in Teaching Hospitals of Kathmandu Valley - Khagi, Bina Rana; Maharjan, Shanti Awale; Bajracharya, Shobha Laxmi; Upadhyay, Radhika; Shrestha, Kabita Bade (Birat Journal of Health Sciences, 2020)
Introduction: Globally, the numbers of elderly population are increasing which is one of the challenges for nurses in health care setting. Nurses' attitude towards elderly people is associated to quality of care they provide. Objective To identify attitude of nurses towards care of elderly people in teaching hospitals of Kathmandu valley. Methodology A cross sectional research design was used to identify attitude of nurses towards care of elderly people. Proportionate stratified random sampling technique was used to select 450 nurses. Ethical approval was taken from Institutional Review Board of Nepal Health Research Council. Data collection was done from 17 April 2017 to 16 April 2018 by using self-administrative questionnaire on socio-demographic characteristics and Multi-factorial Attitude Questionnaires (MAQ) to measure attitude. Data analysis was done using descriptive and inferential statistics. Results The study revealed that 55.3% of respondents had negative attitude and 44.7% had positive attitude towards care of elderly people. There was significant association between age, marital status, studied geriatric nursing and work experiences in nursing with attitudes of nurses. However, there is no association found of ethnicity, religion, type of family, living with elderly, education and currently working with elderly with attitudes of nurses. Conclusion From these findings, it is concluded that about more than half of the nurses had negative attitude towards care of elderly. Gerontological nursing course plays significant role in the attitude of nurses. Therefore, it should be given continuity in all level of nursing education for providing quality care of elderly people.